The Description of Resilient and Competitive Characters of The Senior High School Students in Jakarta - Wulandari, Antonina Pantja Juni (Bina Nusantara University, 2016)
Article described resilient and competitive characters of Senior High School students in Jakarta. This research used the descriptive quantitative research methodology. The population in this research was taken from class 12 students of Senior High School in Jakarta. The sample-taking technique used non-probability sampling. The data collection used the questionnaires given to Senior High School students around Jakarta. The questionnaire consists of two psychological measuring instruments, namely resilient and competitive characters. The measuring instrument for the resilient character was taken from the resilience theory, Resilience Scale (RS), which was developed by Wagnild and Young. The measuring instrument for the competitive character was taken from the achievement motivation theory that is the motivation to encourage a person to be successful in competition with a standard of excellence. Based on the result of this research, the average value of the resilient character is 2.98, while the average value of the competitive character is 2.92. The largest resilient character category is in the high category with the percentage of 59%, while the largest competitive category is in the high category with 224 students and the percentage of 58%. The suggestion for the school is that the teaching of resilient and competitive characters can be presented in the example, definition, discussion, and role-playing. The suggestion for the teacher is to give rewards for students with good characters. The reward is not only for the achievement, but students with good character should be praised to maintain their behavior and use it as the model for other students. The suggestion for the next researcher is that the qualitative research can be used to observe resilient and competitive character from family or school.